Sericulture: Agro-Based Industry For Sustainable Socio-Economic Development: A Review - Ssemugenze, Brian; Esimu, Joseph; Nagasha, Janet; Wandui Masiga, Clet (International Journal of Scientific and Research Publications, 2021)
Silkworm is an important primary productive insect species reared and exploited globally to boost the sericulture industry. Sericulture industry has uplifted the social and economic livelihoods of people across the world by boosting textile industry which is key in plummeting unemployment in developing countries. Livelihood and social improvement achieved through employment opportunities, income generation, economic development, ecological and environmental values, agriculture integration and environment protection. Sericulture directly employs people in mulberry production, leaf and root harvesting, egg production, silk worm rearing, post cocoon handling technologies such as cocoon harvesting and drying, silk reeling, winding, doubling, twisting, warping, weaving, printing and designing, finishing and silk waste processing but also indirectly as traders of silk products, construction of grainage, rearing, ware and post cocoon handling houses, mechanics/operators of silk processing machinery, marketeers of the final products. Sericulture requires minimum investment, simple technology, short gestation period, increased employment opportunities with a high remunerative return fitting the agrarian economy. The industry suits all categories of people ranging from resource poor farmers, landless, children, elderly, youth, male and female and socially under privileged people. This review discusses the socio-economic contributions of sericulture industry as a present and future viable investment for sustainable socio-economic development.
Keywords: Sericulture; Mulberry; Silkworm; Socio-economic Development; Investment